Pengenalan Makanan Bergizi Dengan Menggunakan Media Audio Visual (Video) Untuk Mengembangkan Kemampuan Kognitif Anak di TK Injil Parepei Kecamatan Remboken - Paputungan, Hasnawati (Peneliti.net, 2021)
This study aims to determine whether the introduction of nutritious food using audio- visual media can develop children's cognitive abilities in the Gospel Kindergarten of Parepei Kec. Remboken. This research is a Classroom Action Research (CAR), with the subject of research is children in the Gospel Kindergarten Parepei Kec. Remboken totaling 9 children. The results of the cyclical research by introducing nutritious food using audio-visual media (video) showed an increase in children's cognitive abilities from the first cycle the student learning outcomes reached 44.44%, namely only 4 children who succeeded, while in the second cycle the student learning outcomes reached the success indicator, namely 88 ,88% of 9 students, 8 were successful. So from the results obtained from cycle I to cycle II there was an increase of 44.44%, thus it can be concluded from the results of research on the introduction of nutritious food using audio-visual media (video) to improving the cognitive abilities of children in the Gospel Parepei Kindergarten, Remboken District, in children's learning activities are very important and suitable for use.